Manajemen Strategis Program Pekarangan Pangan Lestari dalam Meningkatkan Ketahanan Pangan di Pekarangan Pangan Lestari Turi Putih di Kelurahan Jrebeng Kidul Kota Probolinggo - Amin Nati Karmilah; Meirinawati Meirinawati; Eva Hany Fanida; Trenda Aktiva Oktariyanda (Lembaga Pengembangan Kinerja Dosen, 2026)
Household food security has become a strategic issue amid socio-economic pressures, climate change, and limited access to nutritious food at the community level. The Sustainable Food Yard Program (Pekarangan Pangan Lestari/P2L) was developed as a community empowerment initiative through the productive and sustainable utilization of household yards. This study aims to analyze the management of the P2L Turi Putih Program in Jrebeng Kidul Subdistrict, Probolinggo City, using a strategic management approach to identify internal and external factors as a basis for formulating program sustainability strategies. This research employed a descriptive qualitative method with data collected through field observations, in-depth interviews with P2L administrators and community members, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing, and further examined using SWOT analysis. The findings indicate that the program’s strengths lie in institutional capacity, human resource quality, managerial independence, and social contributions through environmental education and stunting prevention initiatives. However, major weaknesses include fluctuating member participation and underdeveloped product marketing systems. Externally, opportunities are supported by local government policies, technical assistance from relevant agencies, and the active involvement of the Family Welfare Movement (PKK). Meanwhile, the main threats stem from climate change, flood-prone land conditions, and pest infestations. The sustainability strategies emphasize institutional strengthening, marketing development, human resource capacity building, and environmental risk adaptation to enhance yard-based food security